Fiscal Redistribution and Social Welfare - Coady, David (IMF Working Papers; Working Paper ;, 2019)
Fiscal policy is a key tool for achieving distributional objectives in advanced economies. This paper embeds the discussion of fiscal redistribution within the standard social welfare framework, which lends itself to a transparent and practical evaluation of the extent and determinants of fiscal redistribution. Differences in fiscal redistribution are decomposed into differences in the magnitude of transfers (fiscal effort) and in the progressivity of transfers (fiscal progressivity). Fiscal progressivity is further decomposed into differences in the distribution of transfers across income groups (targeting performance) and in the social welfare returns to targeting due to varying initial levels of income inequality (targeting returns). This decomposition provides a clear distinction between the concepts of progressivity and targeting, and clarifies the relationship between them. For illustrative purposes, the framework is applied to data for 28 EU countries to determine the factors explaining differences in their fiscal redistribution and to discuss patterns in fiscal redistribution highlighted in the literature.